2013
DOI: 10.1590/s0034-75902013000500004
|View full text |Cite
|
Sign up to set email alerts
|

Clusters e APL's: análise bibliométrica das publicações nacionais no período de 2000 a 2011

Abstract: Clusters and LPA's: bibliometric analysis of national publications from 2000 to 2011 Clusters y APL's: análisis bibliométrico de las publicaciones nacionales en el periodo de 2000 a 2011 RAE-Revista de Administração de Empresas | FGV-EAESP RESUMOO objetivo do presente estudo é analisar as publicações científicas sobre clusters e arranjos produtivos locais (APL's) no Brasil, no período de 2000 a 2011. Realizou-se a pesquisa em periódicos, classificados pela Qualis (Capes), das áreas de Administração, Economia e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
12

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 32 publications
0
12
0
12
Order By: Relevance
“…The study contributed to updating the research profile, mainly after the triennium 2013-2015 of Qualis Capes' evaluations. It also added to the mapping of recent Brazilian academic production related to interorganizational networks, completing studies by Alves et al (2013), Andrighi et al (2011), Balestrin et al (2010, Cunha and Carrieri (2003) and Mascena et al (2013). Thus, it is believed that the research reached the proposed objectives, despite its limitations.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The study contributed to updating the research profile, mainly after the triennium 2013-2015 of Qualis Capes' evaluations. It also added to the mapping of recent Brazilian academic production related to interorganizational networks, completing studies by Alves et al (2013), Andrighi et al (2011), Balestrin et al (2010, Cunha and Carrieri (2003) and Mascena et al (2013). Thus, it is believed that the research reached the proposed objectives, despite its limitations.…”
Section: Resultsmentioning
confidence: 88%
“…Polysemy, a feature of the theme (Jarillo, 1988;Powell, 1990;Ring and Van De Ven, 1992), is another factor that emphasizes the importance of analyzing how the subject is being studied. Although previous bibliometric works (Alves et al, 2013;Balestrin et al, 2010;Cunha and Carrieri, 2003;Ferreira et al, 2014;Lima and Campos Filho, 2009;Mascena et al, 2013) have demonstrated the attributes of the analyzed productions, they did not point out how their epistemological characteristics were related, what can be seen as a research opportunity. In addition, considering that the theme in the national scenario is recent, it can be affirmed that there is a structured field of studies in Brazil that needs to be studied, so that even new research problems may arise (Balestrin et al, 2010;Ferreira et al, 2014).…”
Section: Introductionmentioning
confidence: 86%
“…Na medida em que surgem novos arranjos organizacionais que não podem ser inteiramente explicados pelo corpo de teorias econômicas existentes, verifica-se o aumento de interesse no fenômeno de aglomerações geográficas de organizações (TALLMAN et al, 2004;MASCENA;FIGUEIREDO;BOAVENTURA, 2013), que pode explicar o desempenho econômico superior de determinadas regiões (ZENG et al, 2008).…”
Section: Clusterunclassified
“…Mascena et al (2013) concluíram que as abordagens teóricas sobre APLs podem seguir uma linha que enfatiza a competição e externalidades ou uma que destaca a cooperação, a ação coletiva e a confiança entre os agentes.…”
Section: Apeando Do Cavalo: Um Estudo Do Arranjo Vitivinicultor Do Muunclassified